Safety Management in Sustainable Construction Projects: A Conceptual Framework - Hassan, Afaf (International Journal of Global Sustainability, 2021)
Safety management can be utilized effectively in sustainable construction projects, to produce safe sustainable construction projects. This highlights the necessity to gain a better understanding about safety management components with a view to pinpointing existing and future research issues to be addressed. Thus, this systematic review aims to demonstrate a knowledge base for safety management research grounded on the safety management components, and the integration of those components into sustainable construction projects, to produce safe sustainable construction projects. To achieve this, thirty-four peer-reviewed articles were classified into two categories. The first category is about safety management in typical construction projects, and the second category is about safety management in sustainable construction projects. Similar research in the last two decades points out the challenges associated with safety management in sustainable construction projects and the need to understand the associated safety management components that can lead to safer suitable construction projects. In addition, the synthesis suggests the need for a conceptual framework that explains the process of utilizing safety management components in sustainable construction projects to attain the desired safety outcomes in sustainable construction projects. Accordingly, this article provides a conceptual framework that integrates safety management components of traditional construction projects into sustainable construction projects, to achieve safe sustainable construction projects.